Resolving lineage assignation on Mycobacterium tuberculosis clinical isolates classified by spoligotyping with a new high-throughput 3R SNPs based method - Abadia, Edgar (2010)
We developed a new multiplexed-PCR assay to accurately classify Mycobacterium tuberculosis complex (MTC) isolates at the sublineage level by single nucleotide polymorphisms (SNPs). This method relies on 7 SNPs located in different genes of the MTC strains (recC, rec0, recR, ligB, ligC, alkA, and mgtC). Most of these genes are involved in replication, repair and recombination (3R) functions of M. tuberculosis strains, four of the mutations are synonymous, and thus neutral. Genes were chosen as a first empirical approach to assess the congruence between spoligotyping-based phylogeographical classification and SNP typing.This scheme efficiently classifies most of MTC phylogeographical groups: (1) confirming and identifying new sublineage-specific SNPs, (2) unraveling phylogenetical relationships between spoligotyping-defined MTC sublineages, (3) appropriately assigning sublineages to some spoligotypes and reassigning sublineages to other mis-labeled spoligotype signatures. This study opens the way to a more meaningful taxonomic, evolutionary and epidemiological classification. It also allows evaluation of spoligotype-signature significance towards a more comprehensive understanding of the evolutionary mechanisms of the clustered regularly interspaced short palindromic repeat (CRISPR) locus in MTC.